KAMPANYE LINGKUNGAN OLEH KOMUNITAS GENERASI BARU INDONESIA (GENBI) RIAU MELALUI MURAL DALAM MEMBANGUN KEPEDULIAN MASYARAKAT TERHADAP LINGKUNGAN HIDUP DI KOTA PEKANBARU - Nurmailis "; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Generasi Baru Indonesia (GenBI) Riau is a Community Students from State Universities receive Bank Indonesia Scholarships, of which 100 students from each University consist of 50 people. The Riau GenBI Community was established on November 11, 2011. These students not only received scholarships in financial form, but also formed their character especially in the social field. Here GenBI Riau has a work program in the environmental division namely Mural. The purpose of this study was to determine the stages of campaign management, namely: planning, implementation and evaluation in building community awareness of the environment in the city of Pekanbaru through murals.This study uses a qualitative method with a descriptive approach, with data collection techniques, namely through interviews, observation, and documentation, with the number of informants totaling 10 people according to criteria that have been determined through Purposive. The data analysis technique in this study is using themodels Miles and Huberman as well as the validity of data checking techniques, namely the extension of participation and triangulation. The results showed that, in the implementation of the environmental campaign carried out by the Riau GenBI Community, a Campaign Management stage was needed, namely: First, planning phase, in this planning stage there were several things that we had to set beforehand namely: analyzing problems, formulating campaign goals, message themes , programs, target targets, determine strategies and tactics, formulate messages, time, personnel, and budget. Second, the implementation Phase, at this stage is the implementation of a predetermined campaign plan, namely making murals in Tanah Merah, Lapas and in Sukajadi. Third, evaluation phase, this stage is used to see how the campaign was carried out and what results were achieved from the campaign. If this management stage is carried out properly, then a campaign can be achieved in accordance with the objectives previously set. The campaign in this case uses Mural media in the delivery of messages indirectly to the community, especially those in the location of the mural and is a media that is considered effective in delivering a message.